Efficacy of different concentrations of saluyot (Corchorus olitorius L.) leaves extract as an antimicrobial agent against streptococcus mutans an in vitro study - Regine Angelique T. Carandang; Luneta, Criselda P. (Manila Department of Community Dentistry, University of the Philippines Manila, 2015)
INTRODUCTION: Herbal remedies are commonplace in the Philippines, where a huge part of the population cannot afford conventional healthcare methods and this necessitates making use of natural resources to treat various ailments. Corchorus olitorius L., locally known as saluyot, has been found to aid in treating live disorders, gastrointestinal complications, and skin diseases. The present study examined if extract of saluyot leaves can inhibit the growth of Streptococcus mutans, the oral microflora most associated with dental caries, at different concentrations.
METHODS: Extraction was performed with distilled water and 95% ethanol as solvents, and extracts were purified through rotary evaporation and lyophilization. Different concentrations of solutions were prepared at extract-to-solvent ratios of 25mg/mL, 50mg/mL, and 100mg/mL. Growth inhibition was determined through the Kirby Bauer Disk Diffusion Assay. Extracts were applied to the surface of TYC agar inoculated with the test organism using 6mm filter paper disks. 0.12% chlorhexidine gluconate was used as the positive control, and the solvents were used as negative controls. Samples were incubated for 48 hours after which zones of growth inhibition on the surfaces of the culture media were measured.
RESULTS: Among the treatments applied, only the ethanol extract at a concentration of 100mg/mL exhibited zones of inhibition. Statistical analysis showed that the results are significantly different from those produced by the positive control.
CONCLUSION: Crude extract of C. olitorius leaves does not exhibit antimicrobial activity comparable to commercially available chlorhexidine at the concentrations used in the study.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila
Keywords: Streptococcus mutans